Molecular phylogeny of selected mango cultivars based on internal transcribed spacer (ITS) region - Mohd. Arif, Shahkila (2013)
Mango (Mangifera indica L.) is an important species of the family Anacardiaceae and is one of the economical value crops in many parts of the world. Hence, the phylogeny study of this crop is crucial as a step for improvement of its breeding programs. Phylogenetic relationships among 13 Mangifera indica species from Malaysia, Indonesia and Taiwan were inferred by comparing DNA sequence data sets derived from the Internal Transcribed Spacer (ITS) region of nuclear ribosomal DNA (nrDNA) and analyzed using maximum parsimony (MP) method. The results showed that the cultivars were clustered into two major groups. The first group had low bootstrap value which consisted of Malaysian cultivars. The second group divided into two subclades, the first subclade consisted mainly of Taiwan cultivars. The second subclade further divided into two small subclades, which comprised of Indonesian cultivars in the first small subclade and Malaysian cultivar (1) and Indonesian cultivars (2) in another one. The findings suggested that some cultivars had a close relationship with each other even it is originates from different countries which gives better insight with regards to the relationship among these cultivars, thus providing useful information for generating new cultivar.